1993
DOI: 10.1063/1.110338
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation in porous silicon

Abstract: Three lifetime components, one of which is extremely long (25±2 ns), have been observed in experimental studies of positron annihilation in porous silicon, made by anodization in hydrofluoric acid. The Doppler-broadened spectrum of the porous silicon is sharp compared with that of crystal silicon and becomes even narrower in an applied magnetic field. The positronium yield in the porous silicon therefore is concluded from the long lifetime, narrow Doppler spectrum and its narrowing in a magnetic field. The por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Such measurements were performed e.g. by Itoh et al [217] with porous silicon where a quite intense component with the lifetime of 25 ns was observed. The porous structure of silicon depends strongly on the method of preparation, thus a large scatter of data is observed, for example Shantarovich et al [218] The simplest way to observe the defects in thin layers using a slowpositron beam technique is to apply the DBARL method, giving the values of S and W parameters 7 .…”
Section: Surfaces Films Membranes Coatingsmentioning
confidence: 99%
“…Such measurements were performed e.g. by Itoh et al [217] with porous silicon where a quite intense component with the lifetime of 25 ns was observed. The porous structure of silicon depends strongly on the method of preparation, thus a large scatter of data is observed, for example Shantarovich et al [218] The simplest way to observe the defects in thin layers using a slowpositron beam technique is to apply the DBARL method, giving the values of S and W parameters 7 .…”
Section: Surfaces Films Membranes Coatingsmentioning
confidence: 99%
“…The characteristics of positronium (Ps) formation at the defect complexes in the pores can be analysed to draw information on the electronic structure and structural properties of these microstructures. Positron lifetime and Doppler broadening studies have shown Ps formation in PSi and it has been suggested that the inner surface of the PSi is covered with Si-H layers and the pore surface has the atomic structure as that in the hydrogenated amorphous silicon [9][10][11][12]. 2D-ACAR studies have also shown a similar Ps formation in amorphous Si:H [13] and in PSi [14].…”
mentioning
confidence: 89%
“…Recent investigations [3][4][5] carried out to find positron annihilation lifetimes in PSi reveal that there exists an unusually long lifetime component, which originates from positronium formed in the environment of the pores. The results reported by various authors are essentially in agreement.…”
Section: Introductionmentioning
confidence: 98%
“…Positron annihilation lifetime spectroscopy of these samples may serve as a tool to understand some of the details, as this technique is very sensitive to open volume defects. This technique has been widely employed in studying defects in metals and semiconductors including PSi [3,5,6].…”
Section: Introductionmentioning
confidence: 99%